2003
DOI: 10.1002/cii.68
|View full text |Cite
|
Sign up to set email alerts
|

Appreciation of music in adult patients with cochlear implants: a patient questionnaire

Abstract: Many cochlear implant candidates express hopes of enjoying music following implantation. Our aim was to assess the appreciation of music after cochlear implantation in adult patients. Thirty-five out of 45 cochlear implantees (78%) from the North East Programme responded to a questionnaire. Only 16 out of 35 patients (46%) listened to music after implantation. Enjoyment of music on a self-assessment scale was graded a mean of 8.7/10 before deafness but only 2.6/10 after implantation. Listening to music after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 11 publications
1
29
1
Order By: Relevance
“…Research shows that listeners with cochlear implants do not perform well when listening to music [29][30][31]. It is believed that the main reason for this is that listeners with cochlear implants do not perceive pitch well.…”
Section: Discussionmentioning
confidence: 95%
“…Research shows that listeners with cochlear implants do not perform well when listening to music [29][30][31]. It is believed that the main reason for this is that listeners with cochlear implants do not perceive pitch well.…”
Section: Discussionmentioning
confidence: 95%
“…As a result of the broad success of implantation, two trends have emerged: an ever increasing incidence of cochlear implantation in the prelingually deaf population and greater expectations in the postlingually deaf population of what CIs are able to provide (Zwolan et al 1996;Mirza et al 2006). Both these trends encourage clinicians and scientists to once again examine the issue of nonlinguistic sound perception more focally.…”
Section: Introductionmentioning
confidence: 93%
“…Multiple studies have shown that CI recipients experience more difficulties in perceiving music than NH subjects or HA recipients [9,16,20,23,29]. Since music perception skills do not reflect music appraisal or enjoyment, some researchers have addressed this topic by means of questionnaires [7,26,28,30,32,36,37]. Not surprisingly, Gfeller et al [7], Lassaletta et al [32] and Looi and She [28] report that post-implantation, people enjoy music less compared to before receiving their CI, which is confirmed in our study.…”
Section: Music After CImentioning
confidence: 99%
“…A Dutch questionnaire to gain insight in music appreciation was developed based on literature and clinical experience [7,19,26,29,32]. Patients were asked a number of questions regarding their music listening habits before becoming deaf and after cochlear implantation.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation